Visualizing digital transformation in entrepreneurship education: a bibliometric analysis study from 2018 to 2022 - Bulto, Tadesse Weyuma; Chebo, Abdella Kosa; Endeshaw, Berhanu; Werku, Birhanu Chalchisa; Dhliwayo, Shepherd (Frontiers in Education, 2025)
Entrepreneurship education (EE) through digital transformation has recently received scholarly attention, with an exponential increase in publication and citation rates. A bibliometric analysis by visualizing connected networks using Vosviewer is used in the analysis to investigate trends, research topics, and notable works in the field of digital transformation in entrepreneurship education. The comprehensive review scans the evolution of this integrated topic based on 204 papers taken from Web of Science from 2018 to 2022. Results show that digital transformation has significantly impacted various industries and sectors, including entrepreneurship education. The increased scholarly activity in the domain of digital transformation and entrepreneurship education suggests that it is an active and vibrant area of inquiry, attracting the attention and contributions of a diverse range of researchers and practitioners. The integration of digitalization with entrepreneurship education is an important building block for entrepreneurship development. Future research could consider a wider data source to better understand trends in digital integration in entrepreneurship education and its development.